Research on the Creation of Dental Gel with Acyzol - A. L. Golovanenko; I. V. Alekseeva; E. S. Berezina; E. V. Flisyuk; U. V. Nogaeva; I. A. Titovich (Разработка и регистрация лекарственных средств, 2022)
Introduction. An urgent trend in pharmacy is the development of application dosage forms with high bioavailability and long-term effect for use in dentistry. Medicinal preparations in the form of gels have a number of advantages over other traditionally used dosage forms for the prevention and treatment of caries. Acyzol, containing zinc in an ionized state, which is part of such preparations, reduces the risk of caries by suppressing the aggressive properties of soft dental deposits.Aim. On the basis of a step-by-step complex of studies, to develop a dental gel with acisol.Materials and methods. For the study, we used gels with an active pharmaceutical substance – acisol-bis – (1 – vinylimidazole) zinc diacetate (FC 000286-191211.2011, LLC "Makiz-Pharma", Moscow, Russia, series 101218, shelf life 3 years); basic and gel-forming components – Na-KMC C75 (TU 2231-002-50277563-2000, Base of chemical products "Yugreaktiv", Russia, series 151118, shelf life 3 years), methylcellulose – 35 (TU 2231-107-57684455-2003, JSC "UZPH", Russia, series 221218, shelf life 3 years), sodium alginate (TU 15-02-544-83, Base of chemical products "Yugreaktiv", Russia, series 151018, shelf life 3 years) glycerol (FS.2.2.0006.15 "Glycerin", JSC "Kupavnareaktiv", Russia, series 082018, shelf life 3 years), purified water (FS.2.2.0020.18 "Purified water"). During the research, technological, chemical, physicochemical, physical and biopharmaceutical methods were used.Results and discussion. As a result of a complex of experimental studies, a composition was developed, a rational technology was proposed, quality indicators were determined, standardization was carried out and a preliminary shelf life of a new dental gel with acisol was established. In the process of gel standardization, methods have been modified and tested, which can be used to establish the good quality of the gel during its manufacture and storage. The degree of release of acyzol from the gel was determined by the conductometric method, informative, fast and easy to perform. The stability of the gel during storage was investigated and a packaging material was selected that allows keeping the quality indicators within the normal range.Conclusion. The studies carried out have shown the prospects for the development of a gel with acisol. The proposed methods of analysis can be recommended for use to assess the good quality of the gel in the process of manufacturing and storage, as well as for inclusion in regulatory documents.